2010
DOI: 10.1016/j.chemosphere.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Alum application to improve water quality in a municipal wastewater treatment wetland: Effects on macrophyte growth and nutrient uptake

Abstract: Application of low doses of alum to treatment wetlands to reduce elevated outflow winter phosphorus concentrations were tested in mesocosms vegetated with either Typhadomingensis, Schoenoplectus californicus, or submerged aquatic vegetation (SAV) (Najas guadalupensis-dominated). Alum was pumped to experimental units at a rate of 0.91 g Al m(-2) d(-1) and water quality monitored for 3 months. The alum application significantly improved the outflow water quality and overall the growth of the plants was unaffecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Al may have harmful effects on the chlorophyll fluorescence parameters and metabolic enzymes in plants (Wang et al, 2010), where they may be susceptible to the loss of magnesium from the porphyrin ring of the chlorophyll molecule when encountering Al, and the degree of damage is positively correlated with the Al concentration (Zhang and Zhou, 2005). In addition, the physicochemical reactions with Al in water can severely affect the biogeochemical cycling of other elements and the migration of other pollutants (Malecki-Brown et al, 2010;Vicente et al, 2008). Very high levels of residual Al can inhibit the formation of mycorrhiza to interfere with the absorption and transport of Ca, P, and Mg in plants (Baligar et al, 1987), where P and Mg are highly important for chlorophyll synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Al may have harmful effects on the chlorophyll fluorescence parameters and metabolic enzymes in plants (Wang et al, 2010), where they may be susceptible to the loss of magnesium from the porphyrin ring of the chlorophyll molecule when encountering Al, and the degree of damage is positively correlated with the Al concentration (Zhang and Zhou, 2005). In addition, the physicochemical reactions with Al in water can severely affect the biogeochemical cycling of other elements and the migration of other pollutants (Malecki-Brown et al, 2010;Vicente et al, 2008). Very high levels of residual Al can inhibit the formation of mycorrhiza to interfere with the absorption and transport of Ca, P, and Mg in plants (Baligar et al, 1987), where P and Mg are highly important for chlorophyll synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The negative associations between biomass and plant height with the Al contents of the water and sediments in the in situ experiment strongly suggest that the aluminate flocculant significantly degraded the morphological characteristics (P < 0.05), as also shown by Ji et al (2013) and Ahmad et al (2013). Furthermore, Al can limit plant growth by affecting asexual reproduction (Malecki-Brown et al, 2010). The roots are generally considered to be the target organ of Al toxicity (Robert and Richard, 1999;Barcelo and Poschenrieder, 2002), where Al ions are absorbed mainly on the root tips and parts of the lateral roots where cell divide vigorously, thereby severely hindering root cell division and elongation (Barcelo and Poschenrieder, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barkoh et al (2013) suggested that alum may be useful for controlling pH in striped bass production ponds where the inorganic fertilization treatment is applied with inhibition of phytoplanktonic growth as a result of phosphate precipitation. Starting around 1980, it became widely accepted that alum was a major factor used for successful treatment in lake restoration and, consequently, success of aquatic organisms and communities to grow in their habitats (Soltero et al 1981;Malecki-Brown et al 2010). Alum is acidic in water and can reduce total alkalinity by neutralizing carbonate and bicarbonate compounds, with greater efficiency in reducing pH when applied to water with low initial total alkalinity (Barkoh et al 2013).…”
Section: Introductionmentioning
confidence: 99%